Kyungok-go for fatigue in patients with long COVID: Double-blind, randomized, multicenter, pilot clinical study protocol - Jiwon Yoon; Sanghyun Kim; Chan-Young Kwon; Jung Won Kang; Tae-Hun Kim; Sunoh Kwon (PLoS ONE, 2025)
The most common symptom reported by patients after recovery from coronavirus disease 2019 (COVID-19) is fatigue. However, robust clinical evidence supporting the effectiveness of treatments and interventions for fatigue in COVID-19 survivors is lacking. This pilot clinical trial aims to assess the safety and efficacy of Kyungok-go, a herbal preparation targeting fatigue, in patients after recovering from COVID-19. The study will include 100 participants with persistent fatigue for more than 12 weeks after COVID-19 recovery. They will be randomly allocated into two groups: the Kyungok-go group (n =  50) and the placebo group (n =  50). Kyungok-go or placebo will be administered twice daily for 12 weeks, and the participants will be assessed at 4-week intervals. The primary outcome will be the change in the Fatigue Severity Scale score. Secondary outcomes will include cognitive function, physical function, quality of life, depression, sleep quality, medication adherence, and feasibility. This study is the first attempt to investigate the safety and efficacy of Kyungok-go for relieving fatigue related to long COVID. The results are expected to contribute to the establishment of a knowledge base and reveal the potential of herbal medicine prescriptions for managing and recovering from the most common sequelae of COVID-19. Trial registration number: KCT0008789.